Male teachers in elementary education in the public schools of Rio de Janeiro-Brazil and Aveiro-Portugal - Amanda Oliveira Rabelo (Revista Electrónica de Investigación Educativa)
This paper presents a comparative study of male teachers who work in public, elementary-level education in Rio de Janeiro, Brazil, and in Aveiro, Portugal. We intended, fundamentally, to research the reasons and consequences of the professional choice of teachers who are engaged in an area typically associated with women – an association so strong that these teachers seem like a “foreign body” in the daily lives of public elementary schools. We show that the presence of male teachers in elementary education is a way of bringing gender issues to the forefront of education, and that there are other issues and other voices that echo in schools, namely, individuals who are capable of exercising this profession regardless of gender.